2019
DOI: 10.1038/s41598-019-40421-z
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling Duchenne muscular dystrophy in MYOD1-converted urine-derived cells treated with 3-deazaneplanocin A hydrochloride

Abstract: Duchenne muscular dystrophy (DMD) is a severe muscle disorder characterised by mutations in the DMD gene. Recently, we have completed a phase I study in Japan based on systemic administration of the morpholino antisense that is amenable to exon-53 skipping, successfully. However, to achieve the effective treatment of DMD, in vitro assays on patient muscle cells to screen drugs and patient eligibility before clinical trials are indispensable. Here, we report a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…The primers should generate products that can easily be distinguished by size on a MCE system or normal agarose gel electrophoresis if MCE is not available. 16 . Thus, only urine collected from the patient is required to generate the myoblasts, and no invasive procedure is necessary.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The primers should generate products that can easily be distinguished by size on a MCE system or normal agarose gel electrophoresis if MCE is not available. 16 . Thus, only urine collected from the patient is required to generate the myoblasts, and no invasive procedure is necessary.…”
Section: Representative Resultsmentioning
confidence: 99%
“…According to our previous report, we performed direct reprogramming of UDCs into myotubes [21,22]. In short, we transduced MYOD1 into patient-derived UDCs by a retroviral vector containing a doxycycline-inducible MYOD1 expression system, and differentiated MYOD1-transduced UDCs (MYOD1-UDCs) into myotubes by changing the growth medium to differentiation medium containing doxycycline and 5 μM 3-deazaneplanocin A hydrochloride.…”
Section: Myogenic Differentiation Of Myod1-transduced Udcsmentioning
confidence: 99%
“…We performed immunoblotting as described in our previous report [21]. Briefly, total protein was extracted from cultured cells using radio immunoprecipitation assay (RIPA) buffer containing protease inhibitors (Roche, Indianapolis, IN, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the authors assessed if the model was suitable for exon-skipping studies in USCs derived from DMD patients. They showed that AONs targeting DMD exons, including 44, 50, 51 and 55, induced the skipping of the specific targeted exon [31].…”
Section: Application Of Urine-derived Stem Cells In Genetic Diseasesmentioning
confidence: 99%